PENGARUH DEBIT LIQUID TERHADAP EFISIENSI ABSORBSI DALAM PENYISIHAN SO2 PADA SPRAY TOWER ABSORBER - Abdu Fadli Assomadi (Purifikasi, 2005)
One technique to eradicate SO2 contaminant is gas absorbtion system with liquid, for instance Spray Tower Absorber. The research was performed to examine changes value pH adsorber and SO2 efficiency removal within 90 minutes using solar oil 100% with initial pressure of fuel tank = 60, 80 and 100 psi; and flow, water volume, nozzle = 3,5 and 7 L/minutes. Absorber used in this experiment was 0,0006% H2O2 solution. The result shows that pressure and flow absorber affect the absorbtion efficiency for real. Initiate pressure of fuel tank that was greater within time had caused the decrease of absorbtion efficiency faster. The value of pH absorber after being used for absorbtion within 90 minutes was approximately 6,79 because of the raw water buffer originated by acidity and hardness. For efficiency more than 70%, lowest pH absorber was on range 5,59-6,25 and total recirculation for flow 3 L/minutes was maximum 17 times, flow 5 l/minutes was 34 times and for 7 l/minutes was maximum 56 times of recirculation.